Pengaruh Transparansi dan Akuntabilitas terhadap Pengelolaan Dana Desa dalam Mewujudkan Prinsip Good Governance - Meliani Fitrianti; Vita Fitria Sari (Universitas Negeri Padang, 2024)
The main aim of this study was to investigate the impact of transparency and accountability on the effective management of village resources, within the framework of implementing principles of good governance. This research is a case study conducted as a case study in Padang Pariaman Regency. The study encompassed a total of 103